Synthesis of 1,2,3-triazoles containing an allomaltol moiety from substituted pyrano[2,3-d]isoxazolones via base-promoted Boulton–Katritzky rearrangement - Milyutin, Constantine Vyacheslavovich; Komogortsev, Andrey Nikolaevich; Lichitsky, Boris Valerievich (Beilstein Journal of Organic Chemistry, 2024)
For the first time, the interaction of aroyl containing pyrano[2,3-d]isoxazolone derivatives with various hydrazines was studied. It was shown that the considered process includes formation of corresponding hydrazones followed by Boulton–Katritzky rearrangement. As a result, the general method for the synthesis of substituted 1,2,3-triazoles bearing an allomaltol fragment was elaborated. The suggested approach can be applied to various aromatic and heterocyclic hydrazines. At the same time for unsubstituted hydrazine the Boulton–Katritzky recyclization is not implemented. In this case the opening of the pyranone ring was observed leading to pyrazolylisoxazole derivatives. Both types of aforementioned structures were proved by X-ray analysis.
Keywords: allomaltol; Boulton–Katritzky rearrangement; hydrazones; pyrano[2,3-d]isoxazolones; recyclization; 1,2,3-triazoles